Dynamics of Circadian Thalamocortical Flow of Information during a Peripheral Neuropathic Pain Condition - Cardoso-Cruz, Helder; Sameshima, Koichi; Lima, Deolinda; Galhardo, Vasco (Frontiers in Integrative Neuroscience, 2011)
It is known that the thalamocortical loop plays a crucial role in the encoding of sensory-discriminative features of painful stimuli. However, only a few studies have addressed the changes in thalamocortical dynamics that may occur after the onset of chronic pain. Our goal was to evaluate how the induction of chronic neuropathic pain affected the flow of information within the thalamocortical loop throughout the brain states of the sleep-wake cycle. To address this issue we recorded local field potentials – LFPs – both before and after the establishment of neuropathic pain in awake freely moving adult rats chronically implanted with arrays of multielectrodes in the lateral thalamus and primary somatosensory cortex. Our results show that the neuropathic injury induced changes in the number of wake and slow-wave-sleep state episodes, and especially in the total number of transitions between brain states. Moreover, partial directed coherence – PDC – analysis revealed that the amount of information flow between cortex and thalamus in neuropathic animals decreased significantly, indicating that the overall thalamic activity had less weight over the cortical activity. However, thalamocortical LFPs displayed higher phase-locking during awake and slow-wave-sleep episodes after the nerve lesion, suggesting faster transmission of relevant information along the thalamocortical loop. The observed changes are in agreement with the hypothesis of thalamic dysfunction after the onset of chronic pain, and may result from diminished inhibitory effect of the primary somatosensory cortex over the lateral thalamus.